1970
DOI: 10.1111/j.1365-3180.1970.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption and Mobility of Paraquat on Different Soils and Soil Constituents*

Abstract: Summary. The adsorption capacity for paraquat of the following materials was examined: three peat soils; two peaty layers below a turf; a commercial sphagnum peat; grass; Begbroke soil; Fullers’ earth; humic acids isolated from a peat soil; lignin isolated from hardwood sawdust; cellulose powder. The Strong Adsorption Capacity (SAC) of these adsorbents was examined first using a chemical method of analysis and then with the more sensitive Lemna bioassay. Peat soils had an appreciable SAC for paraquat even whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…However, DAMANAKIS et al (1970) observed that 48-hour shaking was required for adsorption of paraquat on HA to reach equilibrium. The speed of adsorption of the bipyridylium herbicide by HA relative to organic and mineral soils is slower (CALDERBANK 1968).…”
Section: A) Equilibrium Timementioning
confidence: 94%
See 4 more Smart Citations
“…However, DAMANAKIS et al (1970) observed that 48-hour shaking was required for adsorption of paraquat on HA to reach equilibrium. The speed of adsorption of the bipyridylium herbicide by HA relative to organic and mineral soils is slower (CALDERBANK 1968).…”
Section: A) Equilibrium Timementioning
confidence: 94%
“…The adsorption of paraquat from the solution phase by the organic matter was demonstrated by the reduction in its phytotoxicity to plants grown in media containing the organic soils (SCOTT and WEBER 1967, COFFEY and W AHREN 1969, DAMANAKIS et al 1970. SCOTT and WEBER (1967) suggested that the bipyridylium cation is adsorbed in exchange for other inorganic cations on the soil organic matter.…”
Section: A) Adsorption On To Soil Organic Mattermentioning
confidence: 97%
See 3 more Smart Citations